Experimental demonstration of a broadband mode converter and multiplexer based on subwavelength grating waveguides. (September 2020) - González-Andrade, David; Dias, Antonio; Wangüemert-Pérez, J. Gonzalo; Ortega-Moñux, Alejandro; Molina-Fernández, Íñigo; Halir, Robert; Cheben, Pavel; V. Velasco, Aitor
Highlights: A broadband and compact mode converter and multiplexer is demonstrated. The device is based on a subwavelength engineered multimode interference coupler. The tip of fabricated Y-junctions excites undesired higher-order modes. Device design was optimized to circumvent these fabrication constraints. The device can be used for future broadband telecom and datacom applications. Abstract: Mode-division multiplexing is a promising solution to enhance the capacity of current photonic integrated circuits and thereby meet the growing demands of telecom and datacom applications. Here, we experimentally demonstrate for the first time, to the best of our knowledge, a compact and broadband mode converter and multiplexer based on a subwavelength engineered multimode interference coupler. Our device was fabricated on a standard 220-nm-thick silicon-on-insulator platform with a small footprint of 38.6 ⨯ 3.7 µm 2 . Experimental results for a complete back-to-back multiplexer-demultiplexer link show an insertion loss <1.1 dB (0.55 dB per device) and crosstalk better than −18 dB for both TE0 and TE1 modes in a 120 nm bandwidth (1.52–1.64 µm).